Great aircraft designs 1900-today - Spilsbury, Richard (Chicago, Illinois Heinemann Raintree, 2016)
Discover the most amazing aircraft designs since 1900. From the Wright brothers' Flyer to supersonic jets, this book charts the story of design that led to some amazing machines. We look at the needs that prompted their design, the designers responsible for breaking boundaries and the technology that made them possible. - Amazon
Science
a gift from book africa
1 2 13
Keywords: Aircraft industry -- History; Airplanes -- History -- Juvenile literature